Socioeconomic position and outdoor nitrogen dioxide (NO2) exposure in Western Europe: A multi-city analysis. (April 2017) - Temam, Sofia; Burte, Emilie; Adam, Martin; Antó, Josep M.; Basagaña, Xavier; Bousquet, Jean; Carsin, Anne-Elie; Galobardes, Bruna; Keidel, Dirk; Künzli, Nino; Le Moual, Nicole; Sanchez, Margaux; et al.
Abstract: Background: Inconsistent associations between socioeconomic position (SEP) and outdoor air pollution have been reported in Europe, but methodological differences prevent any direct between-study comparison. Objectives: Assess and compare the association between SEP and outdoor nitrogen dioxide (NO2 ) exposure as a marker of traffic exhaust, in 16 cities from eight Western European countries. Methods: Three SEP indicators, two defined at individual-level (education and occupation) and one at neighborhood-level (unemployment rate) were assessed in three European multicenter cohorts. NO2 annual concentration exposure was estimated at participants' addresses with land use regression models developed within the European Study of Cohorts for Air Pollution Effects (ESCAPE;http://www.escapeproject.eu /). Pooled and city-specific linear regressions were used to analyze associations between each SEP indicator and NO2 . Heterogeneity across cities was assessed using the Higgins' I-squared test (I 2 ). Results: The study population included 5692 participants. Pooled analysis showed that participants with lower individual-SEP were less exposed to NO2 . Conversely, participants living in neighborhoods with higher unemployment rate were more exposed. City-specific results exhibited strong heterogeneity (I 2 > 76% for the three SEP indicators) resulting in variation of the individual- and neighborhood-SEP patterns of NO2 exposure across cities. The coefficients from a model that included both individual- and neighborhood-SEP indicators were similar to the unadjusted coefficients, suggesting independent associations. Conclusions: Our study showed for the first time using homogenized measures of outcome and exposure across 16 cities the important heterogeneity regarding the association between SEP and NO2 in Western Europe. Importantly, our results showed that individual- and neighborhood-SEP indicators capture different aspects of the association between SEP and exposure to air pollution, stressing the importance of considering both in air pollution health effects studies. Highlights: In Europe, associations between SEP and air pollution are inconsistent. International studies with comparable multilevel data are needed. Associations among 16 European cities were compared showing high heterogeneity. Lower individual-SEP was generally, but weakly, associated with lower NO2 exposure. Lower neighborhood-SEP was generally associated with higher NO2 exposure.